Formation and settling of a disc galaxy during the last 8 billion years in a cosmological simulation - Ceverino, Daniel (Arxiv, 2017)
We present results of a high-resolution zoom cosmological simulation of the evolution of a low-mass galaxy with a maximum velocity of V=100 km/s at z=0, using the initial conditions from the AGORA project (Kim et al. 2014). The final disc-dominated galaxy is consistent with local disc scaling relations, such as the stellar-to-halo mass relation and the baryonic Tully-Fisher. The galaxy evolves from a compact, dispersion-dominated galaxy into a rotation-dominated but dynamically hot disc in about 0.5 Gyr (from z=1.4 to z=1.2). The disc dynamically cools down for the following 7 Gyr, as the gas velocity dispersion decreases over time, in agreement with observations. The primary cause of this slow evolution of velocity dispersion in this low-mass galaxy is stellar feedback. It is related to the decline in gas fraction, and to the associated gravitational disk instability, as the disc slowly settles from a global Toomre Q>1 turbulent disc to a marginally unstable disc (Q=1).